Fresh Osteochondral Allograft for Ankle Arthroplasty - Nichols, Emma Hitt (MD Conference Express, 2014)
A bipolar fresh osteochondral allograft is a treatment option with good clinical outcomes for patients with severe osteoarthritis. Prostheses are widely used to treat severe osteoarthritis; however, fresh osteochondral allografts may be a beneficial treatment alternative, as discussed in this article.